Legumes Research Volume 1 - Jimenez-Lopez, Jose C.; Clemente, Alfonso (IntechOpen, 2022)
This book is a collection of updated studies related to current improvements in legume traits and their agricultural benefits. It discusses the physiological functions, genetics, and genomics of legume crops. Chapters address such topics as genetics and biological insights of seed traits in the context of climate change, improving quality and yields of legume seeds, new genetic resources from diverse germplasms, and agricultural benefits of legumes in agroecosystems.